EMOTIONAL LABOR DITINJAU DARI KEPRIBADIAN BIG FIVE PADA PERAWAT DI RUMAH SAKIT UMUM SARI MUTIARA MEDAN - Nurjannah Hasibuan; Sri Hartini; Rina Mirza (Jurnal Psikologi TALENTA, 2019)
This study aims to find out relationship between dimension big five personality with emotional labor. The research sample was all nurses working at Sari Mutiara Medan General Hospital, which amounted to 115 people, with a total sampling method.The data were collected via emotional labor scale with 48 item and big five personality scale (BFI) with 44 item. The results showed that there was a significant relationship between big five personality with emotional labor. Openness to experience were positively related to emotional labor with correlate coefficient 0.268 and sig. 0.003 (p<0.05), the other dimensions have negative relationships, including extraversion dimensions with correlate coefficient 0.052 and sig. 0.562 (p<0.005), agreeableness with correlate coefficient -0.129 and sig. 0.150 (p<0.05), conscientiousness with correlate coefficient 0.082 and sig. 0.363 (p<0.05) and neuroticism with correlate coefficient -0.104 and sig. 0.245 (p<0.05) were negatively related to emotional labor. The results also showed that the contribution of a given big five personality on emotional labor was 9 percent, while the remaining 91 percent was affected by other factors not examined. From the results, it can be concluded that the hypothesis stating that there is a significance relationship between big five personality and emotional labor.